2019
DOI: 10.1097/aog.0000000000003182
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Estimated Blood Loss in Resource Utilization and Complications of Hysterectomy for Benign Indications

Abstract: has been reviewed by the Editorial Board and by special expert referees. Although it is judged not acceptable for publication in Obstetrics & Gynecology in its present form, we would be willing to give further consideration to a revised version. If you wish to consider revising your manuscript, you will first need to study carefully the enclosed reports submitted by the referees and editors. Each point raised requires a response, by either revising your manuscript or making a clear and convincing argument as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Adhesive disease, being younger than 40 years of age, having a body mass index greater than 35, and the need for a preoperative transfusion were also statistically significantly associated with estimated blood loss greater than 400 mL. [20] Peipert et al [4] demonstrated that patients with excess blood loss >750 mL had a 3.7-fold increase in febrile morbidity after hysterectomy. Surgery affects the coagulation systems and consequent to the increased release of plasminogen activator inhibitor, the fibrinolytic system shuts down, thus leading to coagulopathy and bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adhesive disease, being younger than 40 years of age, having a body mass index greater than 35, and the need for a preoperative transfusion were also statistically significantly associated with estimated blood loss greater than 400 mL. [20] Peipert et al [4] demonstrated that patients with excess blood loss >750 mL had a 3.7-fold increase in febrile morbidity after hysterectomy. Surgery affects the coagulation systems and consequent to the increased release of plasminogen activator inhibitor, the fibrinolytic system shuts down, thus leading to coagulopathy and bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Johns et al [19] reviewed 2,563 hysterectomies performed for non-malignant indications, and they concluded that LAVH was safe with similar complication rates as abdominal or vaginal hysterectomy, and was superior to abdominal hysterectomy (AH). English et al (2019) showed that in their study, there were 18,033 hysterectomies for benign indications from 61 hospitals. [20]The median estimated blood loss was 100 mL, and the 90th percentile estimated blood loss was 400 mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to internal validation, we expect provider involvement information to be reliable and congruent for our historical surgical cohort. [18][19][20][21]…”
Section: Data Sourcementioning
confidence: 99%
“…Qualified nurse abstractors perform appropriate chart abstraction of clinically relevant information regarding surgical cases using a sampling methodology to ensure representativeness of the case mix that have been previously described. [18][19][20][21] The MSQC, due to the sampling methodology and chart abstraction of surgical cases including outcomes information, represented our closest, immediately available ''gold'' standard dataset for the state. We compared the most commonly performed surgeries within the collaborative to our institutional cohort.…”
Section: External Validation With ''Gold'' Standardmentioning
confidence: 99%